Trollhunters - Toro, Guillermo del, 1964-; Kraus, Daniel, 1975- (New York : Disney-Hyperion, 2015)
When a forty-five year old mystery resurfaces that threatens the lives of everyone in his town, San Bernardino teenager Jim Sturges teams up with a band of unlikely heroes to battle the monsters he never knew existed.
Keywords: Trolls -- Fiction; Monsters -- Fiction; Monsters -- Fiction; San Bernardino (Calif.) -- Fiction; San Bernardino (Calif.) -- Fiction